2021
DOI: 10.1063/5.0039388
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of the beryllium acceptor in GaN and a possible route for p-type doping

Abstract: Using theory and experiment, we address a possible p-type doping route of GaN using the Be acceptor. Hybrid functional calculations suggest that straightforward incorporation of Be in GaN will likely lead to compensated high resistivity samples. In this case, beryllium interstitials and nitrogen vacancies are the most likely compensating donors. However, calculations also show that simultaneous incorporation of beryllium and hydrogen in the nitrogen-rich growth regime is likely to lead to the formation of neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…While both light group II atoms can occupy substitutional Ga and interstitial sites, the amphoteric character of Be is considerably more pronounced. Interstitial fractions of 11 Be were found substantially higher than previously for the case of 27 Mg [7,8], which supports theoretical predictions [4,16,19,[21][22][23]25,31] that Be is more prone to self-compensation and thus unsuitable for p-type doping. The exact locations of the interstitial sites of Mg parallel to the c-axis (−0.6±0.14 Å from the O site in p-GaN) and Be (+0.69±0.08 Å) differ, with Be i located closer to the N atoms.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…While both light group II atoms can occupy substitutional Ga and interstitial sites, the amphoteric character of Be is considerably more pronounced. Interstitial fractions of 11 Be were found substantially higher than previously for the case of 27 Mg [7,8], which supports theoretical predictions [4,16,19,[21][22][23]25,31] that Be is more prone to self-compensation and thus unsuitable for p-type doping. The exact locations of the interstitial sites of Mg parallel to the c-axis (−0.6±0.14 Å from the O site in p-GaN) and Be (+0.69±0.08 Å) differ, with Be i located closer to the N atoms.…”
supporting
confidence: 87%
“…From the theoretical side, Be is one of the most studied impurities in GaN and considerable efforts have been made in order to understand its doping behavior [4,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. However, up to now no consensus has been reached regarding theoretical predictions of its acceptor level(s), for which values of <200 meV [16], 60 meV [17], 185-241 meV [18], 183-190 meV [20], 60 meV [22], 120 meV [23], 550 meV [25], 47-93 meV [26], 600 meV [28], 720-800 meV [29], and 205 meV [31] can be found in the literature. One theoretical study [24] and recent experimental results [30] point towards the hypothesis that Be has two acceptor levels, a relatively shallow one (EA≈113 meV), and a second, which is deeper (E A ≈580 meV) and characterized by large lattice relaxations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Demchenko and Reshchikov studied the formation energies of Be‐related energy levels in GaN via Heyd–Scuseria–Ernzerhof (HSE) hybrid functional calculations. [ 27 ] From HSE calculations, they found that the formation energy of Be Ga –H i complex is much lower as compared to the formation energy of Be on a Ga site (Be Ga ) under both N‐rich and Ga‐rich growth conditions, concluding that the presence of hydrogen enhances Be incorporation during growth. In our prior metal modulated epitaxy (MME) work, we did not see any limitation in the incorporation of Be into GaN nor did we see a need to use hydrogen to enhance its incorporation.…”
Section: Introductionmentioning
confidence: 99%